PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN ( Studi Kasus di CV Sawangan Farm Dairy Depok-Jawa Barat) - Surono Surono (JURNAL LENTERA AKUNTANSI, 2020)
This research  was written by Surono,Nirm : 13010382, in May 2017 to November 2017, with the title: Effect of Employment Performance Discipline on CV Sawangan Farm Dairy Depok. This research aims to produce information in the form of a deeper explanation of the effect of Employment Discipline on Employee Performance and obtain the results of data processing on how much the influence of Employment Discipline to Employee Performance. The research method used in this research was quantitative and qualitative data obtained by using descriptive method, with the form of direct field survey and survey through interviews and observations in the form of direct observation. Based on the calculation with simple linear regression equation between X and Y is Ŷ = 64,963 + 0,456X ...... e, this means that if there is an increase in Work Discipline of 1 point then Employee Performance will increase to 64,963 + 0,456 (1) = 65,419. While the result of Hypothesis Testing, the variable of Work Discipline has sig <0,05 meaning significant. While tcount = 9,011 and ttable = 2,0484. Then Work Discipline variables have a positive and significant effect on Employee Performance. And based on the analysis of the correlation coefficient, the value of r = 0.456 means that there is a strong and positive relationship that shows that the increase in Work Discipline can generally improve the Employee Performance. While the result of KD (R ^ 2) = 20,8%. That means 20.8% of independent variables, ie Work Discipline can be explained by dependent variables ie Employee Performance. While the remaining 79.2% is explained by other factors not investigated by this study.Key words: Keywords: Work Discipline, Employee performance